Kim Beerden and Timo Epping (eds) Classical Controversies. Reception of Graeco-Roman Antiquity in the Twenty-First Century. - Roth, Ulrike (Journal of Greek Archaeology, 2023)
pp. 234, 10 ills. Leiden: Sidestone Press Academics, 2022. ISBN: 978-94-6427-036-5, paperback €35.00; 978-94-6427-037-2, hardback €95.00; 978-94-6427-038-9, e-Pdf €15.00.